2023
DOI: 10.3389/fnbeh.2022.1060587
|View full text |Cite
|
Sign up to set email alerts
|

Temporal prediction error triggers amygdala-dependent memory updating in appetitive operant conditioning in rats

Abstract: Reinforcement learning theories postulate that prediction error, i.e., a discrepancy between the actual and expected outcomes, drives reconsolidation and new learning, inducing an updating of the initial memory. Pavlovian studies have shown that prediction error detection is a fundamental mechanism in triggering amygdala-dependent memory updating, where the temporal relationship between stimuli plays a critical role. However, in contrast to the well-established findings in aversive situations (e.g., fear condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…3B,C) (Sun et al, 2021;Todd et al, 2019). Interestingly, the amygdala (AMY) showed a significant positive BOLD contrast during audio-visual stimulation which might support their role in triggering temporal prediction errors (Tavares et al, 2022). Altogether, differences in BOLD activity patterns both before and after training occur across diverse brain networks between mice adopting a target-attending or a target-invariant behavioural strategy during the task, but are particularly prominent in areas involved in processing task-relevant information across learning and differ more significantly after training in the presence of the visually-evoked target stimulus.…”
Section: Stimulus-evoked Fmri Bold Responses With Behavioural Strateg...mentioning
confidence: 80%
See 1 more Smart Citation
“…3B,C) (Sun et al, 2021;Todd et al, 2019). Interestingly, the amygdala (AMY) showed a significant positive BOLD contrast during audio-visual stimulation which might support their role in triggering temporal prediction errors (Tavares et al, 2022). Altogether, differences in BOLD activity patterns both before and after training occur across diverse brain networks between mice adopting a target-attending or a target-invariant behavioural strategy during the task, but are particularly prominent in areas involved in processing task-relevant information across learning and differ more significantly after training in the presence of the visually-evoked target stimulus.…”
Section: Stimulus-evoked Fmri Bold Responses With Behavioural Strateg...mentioning
confidence: 80%
“…3B,C) (Sun et al, 2021; Todd et al, 2019). Interestingly, the amygdala (AMY) showed a significant positive BOLD contrast during audio-visual stimulation which might support their role in triggering temporal prediction errors (Tavares et al, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…The activation cluster in the hippocampus also extends into the amygdala. In previous animal research, it has been shown that temporal prediction errors can trigger memory updating processes in the amygdala in appetitive and aversive association learning contexts 41 , 42 , suggesting a role of the amygdala in predictive processes. In the human context, studies suggest the amygdala to be involved in the processing of body ownership 43 , 44 .…”
Section: Discussionmentioning
confidence: 92%